A study of religiosity and juvenile delinquency in Malaysia - Fahmi, Nor Azmi (Universiti Sains Malaysia, 2006)
Juvenile offending has been a nationally recognized persistent social problem. Current interventions are still distant from comprehensive and holistic resolutions in preventing and decreasing delinquent behaviors. One critical limitation of the existing intervention strategies for decreasing juvenile delinquency is the exclusion of religious factors. For the present study, religion is defined as an integration of four aspects: ( 1) a belief in a transcendent being that provides principles of behavior, purposes of existence, and the meaning of death, (2) a moral system providing principles and ideals of behavior, (3) religious practices based on the belief, and (4) an involvement in and attachment to conventional religious institutions. Some researchers believe that religion is unrelated to delinquency (Hirschi and Stark, 1969; Sutherland and Cressey, 1978). In particular, Hirschi and Stark's finding of the "hellfire and delinquency'' hypothesis, which suggests that religion has no effects on delinquency, has been regarded as an incontrovertible fact for a long time. However, a number of scholars remain confident about the potential beneficial effect that religion has on reducing various types of delinquent behavior (Johnson, 2001; Sloan and Potvin, 1986). Even though there is increasing agreement that religion is an inhibitor of delinquency rather than a contributor, the strength of a religious effect is unclear related to different offense types and religious contexts. According to Bynum and Thompson (1992), in its simplified definition juvenile delinquency is defined as illegal behavior committed by a minor, whilst delinquent behavior is a relative concept, it has meaning only in relation to the laws that apply to a given population at a specific point in time. The present research was designed to investigate the relationship between religiosity and juvenile delinquency. In addition, this study was implemented to analyze the research and literature pertaining to relationship between religiosity and juvenile delinquency. A sample of 150 juveniles were randomly selected by the Prison Officer from Henry Gurney School, Malacca. The juveniles were in range of 15 years to 18 years old. All the respondents were males. The "Religiosity Questionnaires" and the "Self-reported Questionnaires" were used in this study. The hypothesis was tested by the Pearson product moment correlation and t-test analysis using the SPSS/PC + package for statistical analysis. The result of this study indicated a non-significant correlation between religiosity and delinquency. Based on the results, there is no correlation between religious behavior and delinquency, and religious belief and delinquency. The t-test analysis indicated that there is a significant mean difference between 'age group" and religious belief. In addition, there is a significant mean difference between 'number of time enter Youth Rehabilitation Centre' and religious behavior. The result also shows a significant mean difference between 'involvement in gang' and delinquency.